Professional Readiness, Teachers' Attitude and Collaborative Practices of General and Special Education Teachers - del Corro, Eiamin A.; Bustos, Marie Therese A.P. (Philippine Journal of Education Studies (formerly the Education Quarterly), 2014)
Inclusion entails changes in the demographics of the students in the classroom, in the manner lessons are taught and in the roles and responsibilities of teachers. This quantitative descriptive study looks into the professional readiness of 58 general and special education teachers in 10 small private schools within Metro Manila. An adapted National Competency-Based Teachers Standard (NCBTS) was used to measure the respondents’ professional readiness. Majority of the teachers rated themselves as professionally ready to teach in mainstreamed / inclusive classrooms. However, performance indicators specific to dealing with children with special educational needs (SEN), were the least practiced by general education teachers.
Keywords: Professional Readiness, NCBTS, Inclusion